Pengaruh Pengendalian Diri Serta Literasi Keuangan Terhadap Perilaku Pengelolaan Keuangan Pekerja Kota Gresik - Durotul Makkiyah; Wiwik Lestari (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this research is explanatory research used to explain the effect of self-control and financial literacy on financial management behavior. The population in this study were workers who were in the Gresik City area and managed their own finances. This research was cross-sectional because the data were obtained from a large number of questionnaires and were carried out in one period. Meanwhile, this research data collection method uses primary data. Because this study will use a questionnaire so that there are 124 respondents who have met the sample criteria. This study will use a structural equation model (Structural Equation Modeling) as a test tool, namely Partial Least Square (PLS). In this research, the model used is Structural Equation Modeling (SEM). The results of the first variable research prove that self-control has a significant positive effect on the financial management behavior of workers in Gresik City. However, the results of the second variable research prove that financial literacy has no significant effect on the financial management behavior of workers in Gresik City.